INVENTARISASI TUMBUHAN PAKU (Pteridophyta) DI PERKEBUNAN PT BINA SAINS CEMERLANG KABUPATEN MUSI RAWAS - Wahyuningsih W; Merti Triyanti; Sepriyaningsih Sepriyaningsih (Jurnal Biosilampari : Jurnal Biologi, 2019)
This study aims to determine the type of pteridophyta, abiotic factors and the benefits of pteridophyta in PT Bina Sains Cemerlang Plantation, Musi Rawas Regency. The research method used is descriptive qualitative. Data collection techniques in this study were carried out by surveying the research location and then determining the place by using purposive sampling technique. Data analysis techniques with the steps of the methods of observation, documentation, taking pteridophyta and identification. The results of the study of the inventory of pteridophyta at PT Bina Sains Cemerlang Musi Rawas Regency there are 9 families, 19 species, namely Asplenium nidus, Dyplazium pynocarpon, Davallia denticulate, Davallia solida, Nephrolepis biserrata, Nephrolepis cordifolia, Nephrolepis exisplis, Nephrolepis exis. Stenochlaenae palustris, Gleichenia linearis, Lycopodium cernuum,Diplazium esculentum, Drymoglossum piloselloides, Drynaria quercifolia, Phymatosorus scolopendria, Pteris biaurita, Vazaria esculentum, Drymoglossum piloselloides, Drynaria quercifolia, Phymatosorus scolopendria, Pteris biaurita, Vittaria lineculum, Drymoglossum piloselloides, Drynaria quercifolia, Phymatosorus scolopendria, Pteris biaurita, Vittaria lineate, Drymoglossum piloselloides, Drynaria quercifolia, Phymatosorus scolopendria, Pteris biaurita, Selaginella plenary. Soil moisture 8% -68% and soil pH of 7.08-8.00. Benefits of pteridophyta in PT Bina Sains Cemerlang Plantation, Musi Rawas Regency as ornamental plants and as vegetables.